Business ethics and spirituality for corporate sustainability: a Buddhism perspective - Suriyankietkaew, Suparak (Journal of management, spirituality & religion, 2019)
Globally, ethical concerns principally focus on the need for business ethics as well as an emphasis on spiritual leadership to enhance long-term effectiveness and corporate sustainability. This paper responds to a call for further studies of business ethics and spirituality in workplaces and advances the currently limited knowledge in the realm, in particular, from an Eastern Buddhism perspective. Using a case study research approach, this paper investigates how a modern company can ethically and spiritually lead and manage a successful, sustainable business. A Buddhist-based philosophy of "Sufficiency Economy," as advocated by United Nations Development Programme was used as the research framework to examine the philosophy's ethical and spiritual application. The findings suggest that, to achieve long-term corporate sustainability, a successful business enterprise should embrace good ethical and spiritual values via ethics/morality, knowledge, moderation, reasonableness, resilience, compassion and care for its stakeholders. Implications, limitations and future research are discussed.